TINJAUAN KONDISI FISIK ATLET FUTSAL PUTRI KOTA PEKANBARU DI MASA PENDEMI COVID-19 - muhammad, hendri; Vai, Aref; Aspa, Agus Prima (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2023)
This study aims to determine the physical condition of the female futsal players in Pekanbaru during the covid 19 pandemic. The components measured are the most dominant physical condition components, namely strength, speed and endurance. This research is a descriptive research with survey method. Data collection techniques using tests and measurements. The instruments used are push ups, sit ups, 30 meter sprint, illionis agility run, standing long jump and Vo2 Max. Then all data are converted into T-scores and summed. Data analysis used descriptive percentage. The results showed that the physical condition of the women's futsal in Pekanbaru City. Based on the results of data analysis, description, testing of research results, and discussion, namely, the physical condition of Pekanbaru City Women's Futsal players based on the T Score was in the very good category of 0% (0 people), in the good category by 40% (4 people), in the medium category by 20% (2 people), in the less category by 40% (4 people), and in the very poor category by 0% (0 people). Meanwhile, based on the average value, which is 50.0, the profile of the physical condition of the female futsal players in the city of Pekanbaru is in the medium category.